2010
DOI: 10.3892/ol_00000145
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of tissue microarrays compared with whole tissue sections in survival analysis

Abstract: Abstract. Tissue microarray (TMA) is a promising technique in the evaluation of immunohistochemical markers in tumors and may be used as an alternative for whole sections. However, only a few studies have correlated a clinical outcome with both TMA and results obtained from whole sections. This study compared immunostaining for Ki-67 and p16 in TMA (3 cores from each specimen) and whole sections of 171 cases of stage III epithelial ovarian cancer with clinical data. A high expression of Ki-67 was identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 25 publications
0
37
1
Order By: Relevance
“…TMAs were introduced by Kononen in 1998,42 and involves cutting out 0.6–2 mm tissue cores from FFPE tissue and reinserting them into a recipient TMA block containing samples from different patients, thus greatly decreasing the amount of archival tissue required for a particular study, preserving tissue for other research or diagnostic needs, conserving reagents and saving time reviewing the cases. Since only a portion of tissue is analysed, there are concerns if TMAs are representative of the whole tumour,43 44 in particular, in tumours with intratumoural heterogeneity 45 46. However, validation studies comparing TMAs with whole tissue sections have demonstrated a concordance rate of >95% with the use of two to three 0.6 mm cores rather than the use of a single core, as well as minimising decrease in study subjects due to loss of cores during processing 44 47–49.…”
Section: Discussionmentioning
confidence: 99%
“…TMAs were introduced by Kononen in 1998,42 and involves cutting out 0.6–2 mm tissue cores from FFPE tissue and reinserting them into a recipient TMA block containing samples from different patients, thus greatly decreasing the amount of archival tissue required for a particular study, preserving tissue for other research or diagnostic needs, conserving reagents and saving time reviewing the cases. Since only a portion of tissue is analysed, there are concerns if TMAs are representative of the whole tumour,43 44 in particular, in tumours with intratumoural heterogeneity 45 46. However, validation studies comparing TMAs with whole tissue sections have demonstrated a concordance rate of >95% with the use of two to three 0.6 mm cores rather than the use of a single core, as well as minimising decrease in study subjects due to loss of cores during processing 44 47–49.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TMA technology has the advantage that hundreds of specimens are processed simultaneously using identical conditions, thereby conserving reagents, saving time, and decreasing the amount of archival tissue. 24 However, the main limitation of TMA is that the amount of tissue analyzed using this technique is limited and may not be representative of the entire specimen, especially in CRC, in which intratumoral heterogeneity exists. 25 The results of the current study indicate that, although ZNF148 expression in CRC occurs during the progression of normal mucosa to adenocarcinoma, this expression is consecutively downregulated from stage I to stage III CRC and is inversely associated with CRC metastasis and good postoperative survival.…”
Section: Znf148 In Different Stages Of Crc/gao Et Almentioning
confidence: 99%
“…Variability between batches is considerably reduced, since specimens can be simultaneously processed using identical conditions (8,9). Furthermore, the TMA technique significantly reduces the reagents and technical time required for staining (22,23). This is particularly attractive for expensive and time-consuming techniques such as FISH.…”
Section: Anticancer Researchmentioning
confidence: 99%
“…This is particularly attractive for expensive and time-consuming techniques such as FISH. The amount of tissue needed is also reduced (23).…”
Section: Anticancer Researchmentioning
confidence: 99%